2018
DOI: 10.1038/s41598-018-32371-9
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of low grade coal to fluorescent nanocarbon structures and their potential as a glucose sensor

Abstract: Lignite is an abundantly utilized feedstock for the facile synthesis of fluorescent carbon dots and carbon nanomaterials. Its value is appreciated as an energy source for combustion for long time. Herein we report a novel top-down strategy to synthesis lignite based fluorescent nano carbon structures by combined acidic oxidation and chemical reflux. The nanocarbon crystallites in lignite are converted to oxygenated nano carbon dots and graphene sheets. They exhibited stable fluorescence property in the visible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…And to remove lignin, leaves were soaked in hydrogen peroxide (30 vol%) and acetic acid solution (volume ratio of 1:1), and boiled with magnetic stirring at 60 °C for 7 h. Water was used to wash the residue and then filtered until the filter was neutral. The fibers obtained were boiled in 5 wt% of sodium hydroxide solution at 80 °C for 2 h, then, washed with water to neutral and dried in the oven at 80 °C for 24 h. The cellulose fibers from Phoenix Dactylifera L. leaves were obtained 12,13 .…”
Section: Expremental and Methodsmentioning
confidence: 99%
“…And to remove lignin, leaves were soaked in hydrogen peroxide (30 vol%) and acetic acid solution (volume ratio of 1:1), and boiled with magnetic stirring at 60 °C for 7 h. Water was used to wash the residue and then filtered until the filter was neutral. The fibers obtained were boiled in 5 wt% of sodium hydroxide solution at 80 °C for 2 h, then, washed with water to neutral and dried in the oven at 80 °C for 24 h. The cellulose fibers from Phoenix Dactylifera L. leaves were obtained 12,13 .…”
Section: Expremental and Methodsmentioning
confidence: 99%
“…A fine tuning of the emission peaks from the carbon core is observed with the incorporation of tin nanoparticles. Both quantum size effect and surface effect could be responsible for this excitation independent behavior showcased by GTO nanocomposite 5658 .
Figure 8PL spectra of GO and GTO nanocomposite derived from wood and coconut shell.
…”
Section: Resultsmentioning
confidence: 96%
“…Lignite-derived CNs are also a good hyperglycemia glucose monitoring sensor, with a limit of detection of 0.125 mM. 54 This report is first of its kind in a coal-based nanostructure as a fluorescent glucose sensor.…”
Section: Fluorescence Applicationsmentioning
confidence: 87%
“…35 This method introduces negatively charged oxygen functional groups to the synthesized CNs, making them hydrophilic and defective in nature. 54 Ye et al 35 reported the synthesis of GQDs from coal of different ranks, anthracite, bituminous coal, and coke, using a one-step acidic oxidation technique with H 2 SO 4 and HNO 3 (Figure 2). The three precursors were studied in detail using scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), and Raman spectroscopy.…”
Section: Synthesis and Structure Of Cns From Coalmentioning
confidence: 99%
See 1 more Smart Citation